Rancang Bangun Alat Potong Pembagi Buah Sukun Menjadi 8 Bagian - Sudarmono Sudarmono; Jaelani Jaelani; Erina Putri Fitriani (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Cutting is part of cooking activities commonly known as the process of dividing using a knife. As for the cutting tools, there are various types, ranging from manual to automatic, from using knives to sensors. In the report, it is mentioned that the modification of the cutting tool involves an existing fruit cutting tool that was then modified by the author into a tool that divides breadfruit into 8 parts using a spring-based pressing system. This cutting tool is suitable for SMEs such as sellers of fried breadfruit, who can sell or even produce it on a large scale, thereby increasing production capacity. The research method used is an experiment by conducting a literature study, such as collecting data from journals, scientific articles, and books relevant to the discussed topic. The design of the breadfruit cutting tool produces uniform fruit slices in 8 seconds using the breadfruit cutting tool and 1 minute 37 seconds using a kitchen knife. This results in a time difference of 1 minute 29 seconds, making the breadfruit cutting tool much more time-efficient and increasing production capacity compared to using a kitchen knife. One thing to note about this breadfruit cutting tool is the sharpness of its blade, which can be sharpened again using a sharpening tool when it becomes dull.